Pathological cyclic strain promotes proliferation of vascular smooth muscle cells via the ACTH/ERK/STAT3 pathway. Issue 10 (26th June 2018) - Tang, Xia; Liu, Yanyan; Xiao, Qian; Yao, Qingping; Allen, Molly; Wang, Yingxiao; Gao, Lizhi; Qi, Yingxin; Zhang, Ping
Abstract: Abnormal proliferation of vascular smooth muscle cells (VSMCs) is closely related to hyperplasia in hypertension. Our previous study suggested that adrenocorticotropic hormone (ACTH) is mechano‐responsive and may regulate VSMC proliferation. However, the molecular mechanism of VSMC abnormal proliferation induced by conditions of high cyclic strain, especially the role of ACTH in this process, is unclear. Our results revealed that ACTH and its specific receptor melanocortin receptor type 2 (MC2R) were highly expressed in hypertensive rat models. Furthermore, it was demonstrated that the expression of ACTH and MC2R was up‐regulated when exposed to high cyclic strain in vitro, accompanied by abnormal proliferation of VSMCs. Next, it was proved that ACTH‐dependent cell proliferation was related to the phosphorylation of extracellular regulated protein kinases (ERK) and signal transducer and activator of transcription 3 (STAT3). The study also found that ACTH could promote dimerization and glycosylation of melanocortin 2 receptor accessory protein (MRAP), which had a significant effect on MC2R membrane localization and signal activation. When VSMCs were treated with PD98059, a mitogen‐activated protein kinase (MAP kinase) cascade antagonist, it was determined that phosphorylation of STAT3 at Ser727 was dependent on ERK phosphorylation. In summary, these data demonstrated that the abnormal proliferation of VSMCs induced by conditions of high cyclic strain is in part attributed to ACTH and its receptor MC2R. Identifying the mechanism of ACTH‐dependent proliferation of VSMCs may help to provide new therapeutic targets for hypertension. Abstract : Pathological cyclic strain promotes proliferation of vascular smooth muscle cells via ACTH/ERK/STAT3 pathway.